2021
DOI: 10.1016/j.rtbm.2021.100643
|View full text |Cite
|
Sign up to set email alerts
|

Is Local Public Transport unsuitable for elderly? Exploring the cases of two Italian cities

Abstract: The issue of developing environments responsive to the ambitions and needs of older people has become a major concern for social and public policy. According to the activity theory, psychological well-being in old age is based upon the level of activity and social contacts which are kept (Havighurst, 1968). Several researchers (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…As stated by Mariotti et al [91], the conditions of the neighbourhood where older adults live become increasingly important. Fobker and Grotz [92] explored everyday mobility of elderly people in different urban settings, and they found that increasing age is marked by a withdrawal away from the public to the private sphere and this behaviour is reflected by a shrinking of the activity space.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As stated by Mariotti et al [91], the conditions of the neighbourhood where older adults live become increasingly important. Fobker and Grotz [92] explored everyday mobility of elderly people in different urban settings, and they found that increasing age is marked by a withdrawal away from the public to the private sphere and this behaviour is reflected by a shrinking of the activity space.…”
Section: Discussionmentioning
confidence: 98%
“…A second limitation relates to the nature of subjective variables, always influenced by respondents' capacity to adapt to disadvantageous situations [96] and their expectations [97]. Subjective variables notoriously suffer from the tendency on the part of respondents to offer opinions that are implicitly affected by a comparison between their actual state or condition and that of their neighbours [91,98]. To prevent this, our sample was made by considering the years of residence in the neighbourhood as a decisive factor.…”
Section: Discussionmentioning
confidence: 99%
“…This probably happened because older people do generally have fewer digital competencies and they would be more reluctant to participate in an online survey (Politis et al, 2021). Moreover, people who are over 60 years old are already retired and/or rarely use public transport due to certain psy- cho-social barriers which have been identified both in Italy (Mariotti,et al,2021) and in other countries (Al-Rashid et al, 2021). About 60% of the sample are employees, and 15% are freelancers, while the remaining 26% carry out another type of work activity.…”
Section: Data Collectionmentioning
confidence: 99%
“…While the consensus seems to be that seniors tend to have smaller and more compact activity spaces [ 30 , 31 ] they cannot be considered home-bound, as their daily mobility is complex and they show great variance in their activity spaces sizes and shapes [ 32 ]. Previous studies have found that given the proper built environment conditions, seniors can significantly extend their living spaces and even spend more time outside of their residential neighborhood than inside of it [ 33 , 34 ]. That is especially true in walkable and compact cities such as Barcelona where seniors most often used modes of transport -walking and public transport- can take them far within the city.…”
Section: Introductionmentioning
confidence: 99%